Islam, Sexuality, and the “War on Terror”: Luce Irigaray’s Post-Colonial Ethics of Difference (American Journal of Islam and Society, 2014)
This paper explores the reasons why, in the aftermath of 9/11, the interests of Muslim women and Muslim gays have become the civilizing mission in the “war on terror.” In critically examining how pervasive American and European notions of patriotism, liberalism, secularism, and freedom have been couched within the discourseof sexual rights, I explain why this new politics of belonging is inseparable from the new politics of exclusion. This shift has had consequences for progressive social movements. Whereas in social and cultural analysis nationalism has long been associated with male dominance, sexual control, and heteronormativity, certain articulations of feminism and lesbian/gay liberation are now intimately linked with the reinforcement of ethno-cultural boundaries within the western framework. A required allegiance to sexual liberties and rights has been employed as a technology of control and exclusion – what Joan Scott calls a “politics of sexclusion.” This paper elucidates how Muslim gays are joining Muslim women, whose “liberation,” as postcolonial feminists have long argued, has traditionally been used to justify imperialism. I conclude by discussing bodies as a site for the materialization of power and resistance, as related to Luce Irigaray’s notion of an “ethics of sexual difference,” in an attempt to provide the phenomenological conditions of an “alternative space” in which the Muslim as “other” can be heard. The critical role of such a methodology is not to restore a lost historical and obliterated native, but to let her emerge in her difference. This ontology studies the varying ontic meanings of a localized phenomenon, their constitution as different realities and objectivities (i.e., as entities, occurrences, processes, events, (and facts), to shift our focus from identifying the Muslim other to asking “How do we experience the Muslim other as ‘other’?”